Chondroid Lipoma: A Rare Variant of Lipoma - Samadrita Paul; Balaji Pachipulusu; VK Varsha; Poornima Chandra (Journal of Clinical and Diagnostic Research, 2024)
Lipoma is a benign, growing tumour of mesenchymal origin composed of mature fat cells and adipocytes. They can occur in the subcutaneous layer or at intramuscular or intermuscular sites. Oral lipoma, a benign tumour of mesenchymal origin composed of mature adipocytes and usually surrounded by a thin fibrous connective tissue capsule, is rare and mostly found on the buccal mucosa and tongue. Hereby, the authors present a case of Chondroid Lipoma (CL), a very rare subtype of lipoma involving the ventral surface of the tongue in a 50-year-old female patient. The Chondroid Lipoma, a variant of lipoma, is extremely rare in the oral and maxillofacial region containing both embryonal fat and cartilage.